2009
DOI: 10.1111/j.1439-0272.1997.tb00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of hyperactivation, acrosome reaction and motility characteristics of spermatozoa from semen of men of proven fertility and unexplained infertility

Abstract: Semen from men of proven fertility was compared with that of men with unexplained infertility to determine differences in spermatozoal functions such as hyperactivation and acrosome reaction and spermatozoal motility characteristics. The hyperactivated spermatozoa in both groups could be visualised on the monitor of the Computer Assisted Semen Analyser and they exhibited 'circling', 'thrashing', 'starspin' and 'helical' motility patterns and the mean hyperactivation rates were not significantly different. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Inhibition of HAM prevents fertilisation (Stauss et al ., ). Evaluation of HAM by CASA among patients with unexplained infertility has already been described (Mackenna et al ., ; Peedicayil et al ., ; Muratori et al ., ). However, none of these studies were done in IVF patients, so the correlation of HAM to fertilisation rates on the day of OPU could not be compared.…”
Section: Discussionmentioning
confidence: 98%
“…Inhibition of HAM prevents fertilisation (Stauss et al ., ). Evaluation of HAM by CASA among patients with unexplained infertility has already been described (Mackenna et al ., ; Peedicayil et al ., ; Muratori et al ., ). However, none of these studies were done in IVF patients, so the correlation of HAM to fertilisation rates on the day of OPU could not be compared.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, we show here that the percentage of spermatozoa expressing CatSper1 (but none of the parameters evaluated by routine semen analysis) predicts with high accuracy, sensitivity and good specificity, the ability of the sample to reach a level of HA of 10% which distinguishes between donors (young men with no known fertility problems) and subfertile subjects (Alasmari et al, 2013a), reinforcing involvement of the CatSper channel in establishment of HA in human spermatozoa. HA is related to natural fertility (Peedicayil et al, 1997;Mazzilli et al, 2001) and predicts results of IVF (Wang et al, 1993;Sukcharoen et al, 1995;Hirano et al, 2001). Conversely, routine semen analysis is poorly predictive of both natural and in vitro fertilization (Liu and Baker, 2002;Leushuis et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the quantitative assessment of sperm kinetics is of clinical value in identifying men with unexplained infertility and predicting in vivo and in vitro fertility (Consensus Workshop on Advanced Diagnostic Andrology Techniques 1996; Peedicayil et al 1997;Shibahara et al 2004). Despite the documented clinical value of assessment of sperm kinetics, there is an agreement that individual motion characteristics are of little value (Consensus Workshop on Advanced Diagnostic Andrology Techniques 1996).…”
Section: Sperm Motion Kineticsmentioning
confidence: 99%